2002
DOI: 10.1007/s00247-001-0649-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiological findings in NAO syndrome

Abstract: Our study is the first report of the detailed radiological findings of NAO syndrome. In NAO syndrome, both the axial and appendicular skeleton are involved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Gender effects were not observed in the knock-out mice, nor are they reported in NAO patients. Arthropathy, characteristic of human NAO syndrome (12)(13)(14), was not observed in Mmp2 Ϫ/Ϫ mice at any age (data not shown). The Mmp2 Ϫ/Ϫ mice, however, are more susceptible to antibody-induced arthritis (21), suggesting that some additional factors, environmental or genetic, could be involved in the pathogenesis of arthritis in human NAO syndrome.…”
Section: ϫ/ϫ Mice Have Facial Abnormalities and Other Bone Alterationmentioning
confidence: 86%
See 1 more Smart Citation
“…Gender effects were not observed in the knock-out mice, nor are they reported in NAO patients. Arthropathy, characteristic of human NAO syndrome (12)(13)(14), was not observed in Mmp2 Ϫ/Ϫ mice at any age (data not shown). The Mmp2 Ϫ/Ϫ mice, however, are more susceptible to antibody-induced arthritis (21), suggesting that some additional factors, environmental or genetic, could be involved in the pathogenesis of arthritis in human NAO syndrome.…”
Section: ϫ/ϫ Mice Have Facial Abnormalities and Other Bone Alterationmentioning
confidence: 86%
“…Recent linkage analysis suggests that a loss of function mutation of MMP2 causes a human autosomal recessive disorder with multicentric nodulosis, arthropathy with joint erosion, and osteolysis, termed NAO syndrome (10,11). This syndrome also includes facial abnormalities and generalized osteoporosis (12)(13)(14). The finding that NAO syndrome is caused by a loss of MMP-2 activity raises questions about how an ECMdegrading enzyme affects bone volume (10,11).…”
Section: Variae Successful Transplantation Of Wild-type Periosteum Rmentioning
confidence: 99%
“…MMP‐2 in its active form (62 kDa) is the most important MMP in preserving bone mass. Recent evidences have demonstrated that a deficiency of MMP‐2 induces a bone disorder characterized by the destruction of bone tissue in the form of nodules, arthritis and osteolysis (NAO syndrome), which also includes generalized osteoporosis (Al‐Otaibi et al, 2002; Inoue et al, 2006), an occurrence that suggests a more complex role of this gelatinase in the development and maintenance of bone (Mosig et al, 2007). Ovariectomy reduces the activity and expression of MMP‐2 and also the expression of type I and III collagen (Zecchin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, these features are not always present and have occasionally been observed in other osteolysis syndromes. NAO, the most recently created entity, is characterized by moderate‐to‐severe osteolysis and particularly prominent and painful subcutaneous nodules (8–10). The ISDS nosology considers NAO a variant of Torg syndrome, while Winchester syndrome is classified as a separate disease (2).…”
Section: Classification Of Osteolyses As Proposed By the 2001 Nosologmentioning
confidence: 99%